Analysis of the Effects of Rainfall and Groundwater on the Activities of the Baibaoshan Fault. Issue 1 (February 2021) - Hong, Li
Abstract: The Babaoshan fault is one of the main faults in Beijing area. The cross-fault leveling in Niukouyu segment of the fault has been well monitored for many years. At the same time, rainfall and groundwater have obvious influence on leveling data. Based on the qualitative analysis of fault activity reflected by the change of EW direction leveling of Niukouyu segment from 1992 to 1998, a three-dimensional fault model is established to quantitatively explore the weakening effect of rainfall and groundwater on fault activity.